Common Knowledge and Common Rationality Through Provability Logic - Corrado Benassi; Paolo Gentilini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1999)
The paper proposes a formalization of rational agents as first-order consistent formal systems. On this basis we build a notion of common knowledge and common rationality, among agents who are globally inconsistent with each other. An existence theorem for a formal system of common rationality is provided.
Keywords: 330